Effect of surfactant and freeze-thaw stability on coconut milk emulsions / Nur Zainatul Fekehah Abu Bakar - Abu Bakar, Nur Zainatul Fekehah (Faculty of Applied Sciences, 2013)
In this study, the effect of surfactant (Tween 20) and freeze-thaw (FT) stability on coconut milk (CM) emulsions was studied. The objectives were to determine the physical properties and stability of coconut milk emulsions after FT cycle. The study was done by analyzing the CM emulsions in term of viscosity, colour, droplet size and creaming index (CI%). In this study, four types of CM emulsions were prepared which are Blank (fresh coconut milk without addition of Tween 20 and without undergone homogenization process), Homogenized Coconut Milk (H CM), Homogenized Coconut Milk + 0.5% Tween 20 (H CM + 0.5% T20) and Homogenized Coconut Milk + 1.0% Tween 20 (H CM + 1.0% T20). For all analysis, the CM emulsions was analyzed every 4 consecutive days within 16 days. The analysis was carried out after freeze-thaw cycle 1 (FT-C1) and freeze-thaw cycle 2 (FT-C2). The results showed that H CM + 1.0% T20 were the most stable emulsions. For creaming index (CI%), Blank showed the highest creaming index, while H CM + 1.0% T20 showed the lowest creaming index. Low viscosity (LV) Brookfield viscometer was used to determine the viscosity of CM emulsions. The results showed that H CM + 1.0% T20 at FT-C1 had the highest viscosity. For colour analysis, the results showed that H CM +1.0% T20 was lightest in colour compared to HCM + 0.5% T20 and the one without addition of Tween 20. As the day of storage increased, the lightness of all CM emulsions decreased. For every analysis, CM emulsions subjected to FT-C2 was unstable as it pocess larger droplet size, oiling off, low viscosity and decrease in lightness